Tridatu Responsive Inquiry Adaptive Navigation to Enhance Acid-Base Titration Understanding in Bali Schools - Ketut Sepdyana Kartini; I Nyoman Tri Anindia Putra; I Made Marthana Yusa; I Nyoman Widhi Adnyana (Jurnal Edutech Undiksha, 2024)
Students' conceptual understanding of acid-base titration remains a challenge in high school science education. This study aims to assess the effectiveness of the TRIAN model in improving cognitive learning outcomes and user satisfaction. A mixed-methods approach was employed, involving 60 high school students in Bali as research participants. Quantitative data were collected through pre-tests and post-tests, while qualitative data were gathered through observations, interviews, and user feedback. The effectiveness evaluation was conducted using Kirkpatrick’s Evaluation Model, focusing on the Learning level to measure knowledge and skill improvements. The results indicated a 50% increase in students' conceptual understanding, with statistically significant improvements based on paired t-test analysis (p < 0.01). Additionally, findings from the User Experience Questionnaire (UEQ) revealed high satisfaction levels, particularly in the dimensions of attractiveness, stimulation, and efficiency. These findings suggest that the TRIAN model effectively enhances cognitive learning outcomes while integrating cultural values into the learning process. This study concludes that the TRIAN model, supported by TitraSee AR, offers a holistic and engaging approach to science education by bridging modern technology and local cultural traditions. Future research could explore the application of this model in various educational and cultural contexts.